Persepsi Peserta Atas Penyelenggaraan Massive Open Online Course (MOOC) Audit Berbasis Risiko - Evianto, Evan (Cendekia Niaga, 2020)
This study is aimed at identifying and measuring the critical success factors in the implementation of the Massive Open Online Course (MOOC) in technical training for auditor within the Badan Pengawasan Keuangan dan Pembangunan. The study is based on the perceptions of training participants obtained from the answers to the questions in the questionnaire that were filled out when completing the learning session. The questions are divided into five groups of questions which according to the literature are critical success factors including the provision of training, training materials and learning designs, online lecturers / instructors, training infrastructure, and support services. The sample in the study was taken from the MOOC learning session which included 165 responses. The results showed that the training participants perceived that the learning infrastructure factor was the most important determinant of success and was followed by the online instructor / instructor factor. While the training material and learning design factors were perceived by the training participants as the least influencing factors on the successful implementation of the MOOC.